Management of an expansile orbital mass: Plexiform neurofibroma decompression by orbitozygomatic approach. (9th May 2015) - Kovatch, Kevin J.; Purkey, Michael T.; Martinez‐Lage, Maria; Gausas, Roberta E.; Loevner, Laurie A.; Grady, M. Sean; O'Malley, Bert W.; Rassekh, Christopher H.
<x xml:space="preserve">Abstract</x> Neurofibromatosis types 1 (NF‐1) and 2 are significant entities to otolaryngologists because they frequently involve head and neck skin, brain, skull base, orbits, and surrounding neural and vascular structures. We present the case of a 52‐year‐old male with progressive, marked unilateral proptosis due to a multilobulated orbital mass, secondary to biopsy‐proven plexiform neurofibroma (PN). Acute worsening of proptosis leading to corneal abrasion, diplopia, and pain required debulking surgery, for which an orbitozygomatic approach was utilized. Genetic testing for NF‐1 revealed no mutation. This rare case of NF‐negative orbital PN and multidisciplinary treatment considerations for expansile orbital tumors are discussed. Laryngoscope, 125:2457–2460, 2015